EVALUASI PELATIHAN MEMBACA GAMBAR TEKNIK LANJUTAN UNTUK TIM SALES PADA PT. ISTW JAKARTA - Casban ST MT; Umi Marfuah; Ariya Purnamasari Dewi; Didi Sunardi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Advanced technical drawing reading training is a community service activity for the UMJ industrial engineering lecturer team to increase knowledge, develop insight and improve skills in carrying out job duties and responsibilities. This study aims to measure the success rate of training activities based on the evaluation of the CIPP model (context, input, process, product). The design of the evaluation research used the steps of the CIPP model through a qualitative descriptive approach. Partners are the sales team of PT. ISTW Jakarta. Data collection techniques using questionnaires, documentation studies and literature review. The steps of research activities are carried out by determining the focus of the evaluation, designing the evaluation, collecting information, analyzing information and reporting the results of the evaluation. The results of data analysis can be concluded based on the context aspect that the material can attract participants' interest in supporting technical drawing science in accordance with the training program objectives. The input aspect that the speaker can master the material and implementation online is appropriate during the covid-19 pandemic. Aspects of the process that the training material can be understood well and the method of delivering the material systematically. The product aspect is that the training materials are in accordance with the needs in carrying out the work and the results of the training activities felt by the participants can provide benefits for increasing knowledge and broadening insight that can support performance improvement.